THE POSSIBILITY OF DONATION OF ORGANS AND TISSUES - F. Nascimento, Jocinete (Health and Society, 2024)
Organ and tissue donation is a very important subject in our society in general. I intend to discuss what organ donation is. The importance of organ and tissue donation. About the importance of awareness. Organ or tissue donation is an act by which the living individual decides to help in the treatment of other people. Donation may be from organs (kidney, liver, heart, pancreas and lung) or tissue (cornea, skin, bones, heart valves, cartilage, bone marrow and umbilical cord blood). The donation of organs such as the kidney, part of the liver and bone marrow can be done in life. For the donation of organs of deceased persons, only after the confirmation of the diagnosis of brain death can the procedure be performed. The most common is that it happens to people who suffer some kind of accident that causes head trauma, or who are victims of a stroke (stroke) and evolved to brain death. To understand the transplantation of the organs it is necessary to emphasize that the right to separate parts of the living or dead body integrate the personality, according to the understanding of Maria Helena Diniz (2006, p.249). Most of the time, organ transplantation may be the only life expectancy or the opportunity for a fresh start to about 40,000 patients waiting in the queue for Brazil. The gesture of family members who lose a loved one and decide to donate is an act of life, altruism and generosity, as a single donor can benefit at least ten people and make the difference between life and death. Brazil has the largest public transplant system in the world, responsible for financing about 95% of transplants. It is the second country in absolute number of transplants, behind only the United States.